PP.20.12: THE RELATIONSHIP BETWEEN ARTERIAL STIFFNESS AND DIASTOLIC DYSFUNCTION IN ASYMPTOMATIC HIGH-RISK PATIENTS WITH SUBCLINICAL ATHEROSCLEROSIS. (June 2015) - Kim, G.; Kim, C.; Kim, J.; Moon, G.; Yoo, K.; Lee, S.; Moon, D.
Abstract : Objective: Atherosclerosis is associated with arterial stiffness and left ventricular (LV) diastolic function in atherosclerotic cardiovascular disease (ASCVD). However, the relationships between the augmentation index measured at the radial artery (RaAIx) and LV diastolic dysfunction in asymptomatic high risk patients without ASCVD has not been fully established. Figure. No caption available. Design and method: Five hundred and thirty-two statin-naïve patients (male: female ratio 230:302, mean age 56.0 ± 9.2 years) without atherosclerotic cardiovascular disease (ASCVD) were enrolled from subjects who simultaneously received transthoracic echocardiography and non-invasively semiautomated radial artery applanation tonometry (using an Omron HEM-9000AI) in the Department of Internal Medicine, St. Vincent's Hospital, from July 2011 to May 2014. Results: Two hundred and thirteen subjects (male: female ratio 131:82, mean age 58.6 ± 9.6 years) were categorized as the statin benefit group according to the 2013 ACC/AHA guidelines for blood cholesterol treatment, and the remainder were placed in the non-benefit control group. The statin benefit group had significantly higher left ventricular (LV) mass index and early diastolic mitral annular velocity (Em) than the non-statin benefit group. RaAIx and central blood pressure (SBP2) were significantly associated with Em and E/Em in the statin benefit group without ASCVD (Figure). Differences in peripheral and central systolic BP was significantly associated with only Em (r = 0.291, p = 0.009) in the statin benefit group without ASCVD. Conclusions: There are significant relationships between a surrogate marker of arterial stiffness measured at the radial artery and LV diastolic dysfunction in asymptomatic high risk patients without ASCVD.